Effects of induced steric hindrance on the dielectric behavior and H bonding in the supercooled liquid and vitreous alcohol - VIJ, JAGDISH KUMAR (American Institute of Physics, 2001)
The reasons of Debye-type dielectric relaxation in monohydroxy alcohols were investigated by studying the effects of steric hindrance on dielectric behavior and hydrogen bonding in alcohols. Broadband dielectric spectroscopy of supercooled liquid and glassy states of alcohol was performed to study the effect of optical isomers on intermolecular hydrogen bonding. The results showed that the relaxation rates fit the power law equations with critical exponent of 13.4 compared to 2-4 required in mode-coupling theory.
PUBLISHED
Keywords: Condensed matter physics; dielectric relaxation